EDUKASI IBU HAMIL TENTANG TANDA BAHAYA KEHAMILAN PADA WARGA DUSUN PONDOK BUAK DESA BATU KUMBUNG - Nurul Hikmah Annisa; Baiq Ricca Afrida; Ni Luh Sari Setia Wati (Jurnal LENTERA, 2022)
Pregnancy is a natural and physiological process. Every woman who has healthy reproductive organs, if she has experienced menstruation and has sexual relations with a man whose reproductive organs are healthy, there is a very high possibility of pregnancy (Mandriwati, et al 2017). Normal pregnancy will take place within 40 weeks or 10 lunar months or 9 months according to the international calendar. Pregnancy is divided into 3 trimesters: 1. the first trimester lasts for 12 weeks, 2. the second trimester is 15 weeks (13 to 27 weeks) and 3. the third trimester is 13 weeks (28 to 40 weeks) (Prawirohardjo, 2014). Knowledge of pregnant women about the danger signs in pregnancy is one of the factors that can affect the alertness of pregnant women to the danger signs of pregnancy. To prevent the occurrence of danger in pregnancy, pregnant women need to have regular antenatal care checks at health facilities. This study aims to determine the relationship between knowledge of pregnancy danger signs and compliance with the implementation of antenatal care (ANC) in pregnant women. There is a strong relationship between knowledge of the danger signs of pregnancy and adherence to antenatal care for pregnant women in Pondok Buak Hamlet.